Pengaruh Insentif Dan Motivasi Kerja Terhadap Kepuasan Kerja: Gender Sebagai Variabel Kontrol (Studi Pada Puskesmas Ngadirejo Temanggung) - Alfiyana Durrotun Nafisah; Prayekti Prayekti; Didik Subiyanto (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine and analyze the role of incentives and work motivation on job satisfaction with gender as a control variable conducted at the Ngadirejo Health Center, Temanggung. This research uses quantitative methods with a population of all employees of the Ngadirejo Health Center, totaling 66 people. Data from the population was taken using a census data collection method with a questionnaire survey. Data analysis included validity and reliability tests, classical assumption tests, multiple regression analysis, and t-tests using the SPSS 25 software application. The results of the study stated that incentives had a positive and significant effect on job satisfaction, and motivation had a positive and significant effect on job satisfaction. Then for incentives and motivation, it can be stated that they simultaneously influence job satisfaction. The control variable shows that the male gender has no significant effect on job satisfaction but the female gender has a significant effect on job satisfaction.